The Role of Village-Owned Enterprises (BUMDES) in Local Economic Empowerment: Analysis and Recommendations - Ridhowati, Ridhowati (Riviera Publishing, 2024)
This research aims to explore the role of Village-Owned Enterprises (BUMDes) in enhancing the local economy in a village. The study employs a quantitative method, collecting data through questionnaires distributed to 100 respondents involved in BUMDes activities. The statistical analysis includes descriptive analysis, validity and reliability testing, as well as inferential analysis such as t-tests and ANOVA to identify differences in knowledge and participation based on demographic variables. The findings indicate that the existence of BUMDes significantly enhances community knowledge and participation in economic programs, as well as positively impacts income growth and access to services. The findings also suggest significant differences in levels of knowledge and participation based on gender and age groups, with males tending to have higher knowledge and younger respondents being more actively involved. Therefore, this study recommends that BUMDes managers consider the demographic characteristics of the community when designing more inclusive programs that meet their needs. With the optimization of BUMDes's role, it is expected that the village economy can continue to grow and provide greater benefits to the community. This research provides important insights for the development of BUMDes and local economic empowerment strategies in the future.